Extra-ocular sebaceous carcinoma - A rare case report - Manda Sindhura; Tummidi Santosh; Jarang Rajesh Kumar; Arundhathi Shankaralingappa; Naresh Kumar Pannerselvam; Pavithra Balakrishna (Indian Journal of Pathology and Microbiology)
Sebaceous gland carcinoma is a rare and aggressive skin cancer derived from the sebaceous glands. Sebaceous carcinomas are divided into those occurring in ocular (75%) and extra-ocular locations. A 45-year-old female patient presented with rapidly growing swelling over the upper back region. It was provisionally diagnosed as an infected sebaceous cyst, and an excision biopsy was received in the pathology department. Histopathology was reported as sebaceous carcinoma, Grade II, Stage P T3 Nx. Immunohistochemistry was positive for epithelial membrane antigen. Sebaceous carcinoma accounts for 0.2–4.6% of all malignant cutaneous neoplasms, and the estimated rate of occurrence is only 1–2 per 1 million individuals per year. These tumors frequently present with a painless sub-cutaneous nodule, but they can also present as pedunculated lesions, irregular mass, or diffuse thickening of the skin. Hence, they are misinterpreted as other benign tumors or inflammatory conditions, thereby leading to delay in diagnosis, inappropriate treatment, increased morbidity, and mortality.